Inter-annual variability of catchment water balance in a montane spruce forest. Issue 10 (27th July 2022) - Skalova, Veronika; Dohnal, Michal; Votrubova, Jana; Vogel, Tomas; Sanda, Martin
ABSTRACT: Climatic conditions in temperate montane forests vary over multiple temporal scales. This study examines the effects of inter-annual climatic variability on the long-term water balance of a small headwater catchment with gradually changing vegetation characteristics. The research is based on direct observations of basic hydrological variables (precipitation, stream discharge), and process-based modelling of difficult-to-measure variables (forest transpiration, wet canopy evaporation, snow sublimation). The catchment water balance is evaluated in terms of the catchment water storage. The uncertainty of the estimated storage changes is expressed as a convolution of partial uncertainties associated with the individual components of catchment water balance. The results suggest a significant decrease of catchment water storage over the study period. The decrease is assumed to be caused by increasing winter temperatures, resulting in a more frequent occurrence of liquid precipitation and less prominent spring snowmelt. Considering vegetation's conservative water-balance management proved essential for the studied environment.